2018
DOI: 10.1007/s40090-018-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of ZnO nanorods as an adsorbent material for the removal of As(III) from aqueous solution: kinetics, isotherms and thermodynamic studies

Abstract: Removal of metals from wastewaters causes a big concern from the environmental point of view due to their extreme toxicity towards aquatic life and humans. Application of As(III) from aqueous solution by ZnO nanorods as adsorbent has been investigated in the present study. The synthesized nanorods were characterized by XRD, FT-IR spectroscopy, SEM, and thermogravimetric analysis. Optimum biosorption conditions were determined with respect to pH, adsorbent dose, contact time, and temperature. The experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 62 publications
6
36
2
Order By: Relevance
“…3e). This result is consistent with other studies depicting the endothermic adsorption of As(III) 28 , azo dyes 29 and, Pb(II) ions 71 on ZnONPs. It is important to mention that ∆H o values in the range of 2.1 -20.9 kJ/mol and 80 -200 kJ/mol are attributed to physisorption and chemisorption respectively 84 .…”
Section: Kinetics and Thermodynamics Of Adsorptionsupporting
confidence: 93%
“…3e). This result is consistent with other studies depicting the endothermic adsorption of As(III) 28 , azo dyes 29 and, Pb(II) ions 71 on ZnONPs. It is important to mention that ∆H o values in the range of 2.1 -20.9 kJ/mol and 80 -200 kJ/mol are attributed to physisorption and chemisorption respectively 84 .…”
Section: Kinetics and Thermodynamics Of Adsorptionsupporting
confidence: 93%
“…The move of the peak from 1078.21 to 1080.14 cm −1 suggests the contribution of the C-O set in limited Ni (II).These results are in agreement with a pervious reported study [27]. c) Surface morphology test SEM measurement of the able to adsorb substances is the most significant estimation since the adsorption limit principally relies upon structure and porosity for the surface [20,27].…”
Section: Adsorption Thermodynamicssupporting
confidence: 90%
“…Also, a wide absorption band around 428-570 cm −1 is referred to the mineral zinc-oxide extension group. The results of FT-IR spectra for zinc oxide nanoparticles are in a good agreement with study [20]. Figure 2b depicts the FT-IR spectra after Ni(II) filled, the wide peak at 3429.43 cm −1 which is related to O-H stretching that present in alcohol and climbs during adsorption method.…”
Section: Adsorption Thermodynamicssupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to these, certain nano ZnO doped with other metals have also been reported as adsorbents (Ghiloufi et al, 2016;Meng et al, 2015). Similarly, investigations involving ZnO nano rods were also carried out for the removal of toxic metals (Ghaedi et al, 2015;Yuvaraja et al, 2018). But, however, study related to ZnO with similar morphology as in the present study for chromium adsorption is found to be scarce in literature.…”
Section: Introductionmentioning
confidence: 79%